Nanofiber-based composite material with spider web structure as well as preparation method and application of nanofiber-based composite material

Preparation of polymal -fiber membrane mixed with CU2+through electrostatic spinning technology, combined with the treatment of copper electrical ink and hydrogel, forming a "cobweb structure" nano -fiber -based composite material, solving the problem of low sensor sensitivity and poor stability. It realizes high sensitivity and flexible sensors for long -term service.

CN119352302APending Publication Date: 2025-01-24ZHONGYUAN ENGINEERING COLLEGE

Patent Information

Application Number
CN202411476610.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing fiber-based sensors have low sensitivity and poor long-term use stability, making it difficult to build a flexible sensor with stable signal output, high sensitivity, long-term service and strong stability.

Method used

Cu2+-doped polylactic acid porous nanofiber membranes were prepared using electrospinning technology, and copper conductive ink was sprayed during the spinning process, and then polyacrylamide/sodium alginate/chitosan hydrogel solution was sprayed and dried and UV treated. Connected to form a nanofiber-based composite material with a "spider web structure".

Benefits of technology

Achieve high -sensitivity, thin toughness, fatigue, fatigue, and long -term service -based strain sensor. The resistance changes remain stable after stretching in the major strain cycle. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352302A_ABST
    Figure CN119352302A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sensors and intelligent wearable electronics, and discloses a nano-fiber-based composite material with a cobweb structure as well as a preparation method and application of the nano-fiber-based composite material. Preparing a Cu < 2 + >-doped polylactic acid porous nanofiber membrane by utilizing electrostatic spinning, and spraying copper conductive ink in the spinning process; and then hydrogel is sprayed and cross-linked to obtain the nanofiber strain sensor with a cobweb structure. Under the action of strong surface energy of a porous nanofiber interface, the copper conductive ink forms a linear continuous conductive area depending on fiber appearance, a flaky conductive area is constructed by enrichment distribution of the conductive ink at the junction of fibers, and the linear and flaky areas are in network connection in the polylactic acid porous nanofiber membrane. A bionic cobweb structure electric signal transmission structure model is constructed, hydrogel is sprayed to enable the structure to be crosslinked and wound, and the nanofiber-based high-sensitivity strain sensor which is high in toughness, resistant to fatigue and excellent in human skin attaching capacity is obtained. The preparation method is simple, low in cost, high in toughness, resistant to fatigue, excellent in human skin attaching capacity, high in sensitivity and wide in application range, and can be used for physiological health detection and wearable electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sensors and intelligent wearable electronic technologies, and in particular to a "spider web structure" nanofiber-based composite material and a preparation method and application thereof. Background Art

[0002] Flexible electronic products are widely used in smart wearables, healthcare, human-computer interaction and other fields. The construction of fiber-based conductive devices has become the focus of scholars' research. Strain sensors require that their components have a certain degree of ductility and conductivity. Fibers and their aggregates have good ductility and become a good substrate for strain sensors. Many people have proposed that yarns, knitted fabrics, woven fabrics, non-woven fabrics, etc. in the textile field should be treated with conductive modification and applied to the construction of strain sensors.

[0003] Nanoscale electrospun membranes have also been proposed by relevant scholars as highly sensitive strain sensors due to their porosity and low modulus characteristics. For example, Tao et al. prepared BC / PPy flexible conductive fiber membranes using in-situ polymerization. Polypyrrole conductive particles can form a uniform and dense conductive layer on the surface of BC nanofibers. Although the resistance value is only 12Ω, when the polymer covers the fiber surface, it will affect the fiber morphology and pore structure, and the cross-linking density will lead to enhanced rigidity of the material, making the material harder, thereby affecting the flexibility and long-term serviceability of the material. After the stacking structure of nanofibers and nanofiber aggregates is subjected to multiple deformations, the nanofibers are prone to dislocation, slippage and fracture, resulting in structural evolution, which can easily affect the stability of the functional properties of the material. Chinese invention patent CN115096480A discloses a method for preparing a flexible capacitive pressure sensor. The invention obtains a TPU nanofiber film doped with silver nanoparticles by electrospinning, and then encapsulates it with PDMS, so that the sensor has high sensitivity and wide sensing range. However, due to the poor biocompatibility of PDMS, the skin-fitting effect and adhesion in actual human body monitoring are weak, and in actual use, under large deformation, the continuous conductive network formed by TPU will break or permanently deform, affecting the durability and recyclability of the sensor. Polylactic acid (PLA) has attracted much attention in the research of flexible sensors due to its excellent biocompatibility and special porous structure. As a bio-based material, PLA can be decomposed into non-toxic lactic acid in the environment; after the conductive particles are doped, when there is strain, the pores are deformed to aggregate the conductive particles inside, forming a semi-continuous conductive network, which allows it to generate electrical signals under small deformation, making it highly sensitive. Kim et al. used electrospinning technology to prepare PLA / silver nanoparticle composite nanofiber membranes. PLA and silver nanoparticles were mixed by electrospinning to form fibers under a high electric field. The doping of silver nanoparticles increased the conductivity of the nanofiber membrane from 0.1S / m to 3.5S / m, indicating that the composite material has good conductivity and toughness. However, silver nanoparticles are expensive and easily oxidized in the air, which affects the application of sensors in long-term service. Therefore, how to use the characteristics of nanofibers and their aggregates to construct a flexible sensor with stable signal output, high sensitivity, long-term service and strong stability has become a technical problem. Summary of the invention

[0004] In order to solve the technical problems of low sensitivity and poor long-term stability of fiber-based sensors, the present invention proposes a "spider web structure" nanofiber-based composite material and its preparation method and application. The strain sensor prepared with the composite material has the characteristics of high sensitivity, thinness and toughness, fatigue resistance, and long-term service (when it is cyclically stretched 1000 times under large strain (fixed elongation 20%), it can still maintain the stability of resistance change).

[0005] To achieve the above object, the technical solution of the present invention is implemented as follows:

[0006] A method for preparing a "spider web structure" nanofiber-based composite material, comprising the following steps:

[0007] (1) Preparation of doped Cu by electrospinning 2+ Polylactic acid porous nanofiber membrane was sprayed with copper conductive ink during electrospinning to prepare Cu-doped 2+ Polylactic acid-based copper-coated porous nanofiber membrane;

[0008] (2) Spraying the polyacrylamide / sodium alginate / chitosan hydrogel solution onto the Cu-doped 2+ A polylactic acid-based copper-plated porous nanofiber membrane is then dried and UV-crosslinked to obtain a "spider web structure" nanofiber-based composite material.

[0009] The spinning solution for electrospinning in the above step (1) is prepared by dissolving polylactic acid and copper sulfate pentahydrate in a mixed solvent of dichloromethane and N,N-dimethylformamide.

[0010] The mass ratio of the above-mentioned dichloromethane and N,N-dimethylformamide is (7-9):1; the concentration of polylactic acid in the spinning solution is 8-9wt%, and copper sulfate pentahydrate accounts for 3-7wt% of the mass of the polylactic acid.

[0011] The electrospinning process parameters in the above step (1) are: flow rate of 1-1.5 mL / h, voltage of 18-20 kV, receiving distance of 15-18 cm, ambient temperature of (25±1)° C., relative humidity of 55%±1%, and spinning in the dark.

[0012] The interval of spraying the copper conductive ink in the above step (1) is 1 spraying every 30-60 minutes, and the spraying is 4-6 times.

[0013] The preparation method of the polyacrylamide / sodium alginate / chitosan hydrogel solution in the above step (2) is as follows: acrylamide and sodium alginate are dissolved in deionized water, and ammonium persulfate, N,N-methylenebisacrylamide and chitosan are added thereto to obtain the polyacrylamide / sodium alginate / chitosan hydrogel solution.

[0014] The content of the chitosan is 7.5-10wt% of the total solid mass.

[0015] The drying temperature in the above step (2) is 60°C and the drying time is 40-50 minutes; the power of the UV lamp in the UV crosslinking is 20-30W / cm 2 , the cross-linking time is 2h.

[0016] A nanofiber-based composite material with a "spider web structure" is prepared using the above-mentioned preparation method.

[0017] The above-mentioned "spider web structure" nanofiber-based composite material is used in strain sensors.

[0018] Furthermore, the strain sensor prepared from the above-mentioned "spider web structure" nanofiber-based composite material is used in human motion and physiological monitoring.

[0019] The present invention adopts electrospinning technology and uses a double solvent method (DCM / DMF mixed solvent) to prepare doped Cu 2+ The polylactic acid porous nanofiber membrane is formed, and copper conductive ink is sprayed during the formation of the porous nanofiber membrane. Due to the strong surface energy of the porous nanofiber interface (the porosity of the nanofiber membrane is increased from 70.95% to 81.95%, and its contact angle is also reduced from 129.95° to 105.94°. The higher the porosity, the smaller the contact angle, and the greater the specific surface energy of the fiber), the copper conductive ink depends on the fiber surface to form a "linear continuous conductive area", and the enriched distribution of the conductive ink at the junction of the fibers constructs a "sheet conductive area". The network connection of the "line" and "sheet" areas inside the polylactic acid porous nanofiber membrane constructs a bionic "spider web structure" electrical signal transmission structure model. The structure is cross-linked and entangled by spraying a hydrogel with excellent elasticity to obtain a nanofiber-based composite material with strong toughness, fatigue resistance, and excellent human skin adhesion.

[0020] The beneficial effects produced by the present invention are:

[0021] (1) The present invention proposes a method for preparing a "spider web structure" nanofiber composite material, which specifically includes the preparation of a PAM / SA / CS hydrogel solution, doping with Cu 2+Preparation of polylactic acid spinning solution, electrospinning + spraying of copper conductive oil, spraying of hydrogel solution, drying and UV cross-linking. In the electrospinning process, the copper ions added to the spinning solution form the transmission of electrical signals inside the nanofibers, which is beneficial to the improvement of electrical conductivity (reduction of resistance); the porous polylactic acid nanofibers constructed with double solvents have a porous feature that increases the surface energy of the nanofiber interface, increases the copper loading, and at the same time increases the probability of copper at the fiber interface at the porous part and the connection with the copper inside the fiber, thereby increasing the electrical conductivity of the material. The porous nanofibers and nanofibers interact to form a synergistic strong surface energy effect, forming a copper conductive area with a flaky distribution, which is beneficial to the multi-dimensional and multi-directional transmission of electrical signals at the nanofiber interface, improving the electrical conductivity (resistance is 62-77Ω) and sensitivity (GF=30-74). At the same time, this interconnection method forms a "spider web structure" transmission model in space. As an elastomer, hydrogel has excellent fatigue resistance within a certain range. Hydrogel is cross-linked with nanofibers, forming elastic deformation during stretching, which can be quickly restored after the external force is removed. During the deformation process, nanofibers and their aggregate fibers do not undergo irreversible dislocation or slippage under the cross-linking of hydrogel, which effectively guarantees the stability of electrical signals of sensors prepared with them during repeated use. At the same time, hydrogel has excellent skin adhesion ability, which is conducive to high-quality signal collection.

[0022] (2) The preparation method of the "spider web structure" nanofiber-based composite material and the strain sensor based thereon proposed in the present invention is simple, low-cost, highly flexible (bending resistance length is only 0.99 cm), strong toughness (tensile strength at break is enhanced from 10% of the untreated material to 51% of the treated material), fatigue-resistant (after 1000 repeated stretching cycles with a fixed elongation of 20%, the output electrical signal has no obvious change, and the material has no breakage and obvious change, maintaining the integrity of the structure), excellent human skin adhesion ability (the hydrogel is attached to dynamic areas of human joints such as elbows or knees, and bending and stretching actions are performed. Under the condition of skin activity and large deformation, the adhesion is still maintained for 10 hours), high sensitivity (GF=30-74), wide range of applications, and can be used for physiological health detection and wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 It is a schematic diagram of the "spider web structure" transmission model of the present invention.

[0025] Figure 2 This is the SEM morphology of the “spider web structure” nanofiber-based composite material prepared in the present invention.

[0026] Figure 3 The porosity and contact angle of the "spider web structure" nanofiber-based composite materials prepared in Example 1 and Comparative Example 2.

[0027] Figure 4 The anti-bending length of the "spider web structure" nanofiber-based composite material prepared in Example 1 and Comparative Example 4.

[0028] Figure 5 These are the stress-strain curves of the “spider web structure” nanofiber-based composite materials prepared in Examples 1-3 and Comparative Examples 1, 3, and 4.

[0029] Figure 6 The resistance of the “spider web structure” nanofiber-based composite materials prepared in Examples 1-3, Comparative Example 1, Comparative Example 3 and Comparative Example 4.

[0030] Figure 7 The sensitivity of strain sensors prepared using the "spider web structure" nanofiber-based composite materials prepared in Examples 1-3, Comparative Example 1, Comparative Example 3 and Comparative Example 4.

[0031] Figure 8 This is a test curve of the fatigue resistance of the “spider web structure” nanofiber-based composite material prepared in Example 1.

[0032] Fig. 9 The strain sensor prepared by the nanofiber-based composite material with the "spider web structure" prepared by the present invention is applied in human body motion detection.

[0033] Fig.10 The invention discloses an application of a strain sensor made of a nanofiber-based composite material with a "spider web structure" prepared by the present invention in human pulse detection. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] The preparation method of a "spider web structure" nanofiber-based composite material of this embodiment comprises the following steps:

[0037] (1) Preparation of polyacrylamide / sodium alginate / chitosan (PAM / SA / CS) hydrogel solution: Weigh 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA), add 43 mL deionized water, and after complete dissolution, add 0.0215 g ammonium persulfate (APS) and 0.0092 g N,N-methylenebisacrylamide (MBAA) respectively, and add chitosan accounting for 7.5 wt% of the total solid mass, stir at room temperature until completely dissolved, and obtain a PAM / SA / CS hydrogel solution.

[0038] (2) PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 9:1), the mass concentration of PLA spinning solution was 8wt%, and copper sulfate pentahydrate (CuSO4·5H2O) accounting for 5% of the mass of polylactic acid was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of a flow rate of 1mL / h, a voltage of 20kV, a receiving distance of 18cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process must be carried out in the dark to prevent DCM from photocatalytic reaction during the spinning process). During the spinning process, a spray gun (W-101) was used to spray copper conductive ink, spraying once every 60min, and spraying 4 times to obtain Cu doped 2+ Polylactic acid-based copper-plated porous nanofiber membrane. The PAM / SA / CS hydrogel solution was sprayed on the Cu-doped 2+ The polylactic acid-based copper-plated porous nanofiber membrane was dried at 60°C for 45 min, and the dried sample was placed under a UV lamp (power 20 W / cm 2 ) and irradiated for 2 hours.

[0039] The doped Cu was prepared by electrospinning using a dual solvent method (DCM / DMF mixed solvent) 2+ The polylactic acid porous nanofiber membrane is formed, and copper conductive ink is sprayed during the porous nanofiber membrane forming process. Due to the strong surface energy of the porous nanofiber interface, the copper conductive ink depends on the fiber surface to form a "linear continuous conductive area", and the enriched distribution of the conductive ink at the junction of the fibers constructs a "sheet conductive area". The network connection of the "line" and "sheet" areas inside the polylactic acid porous nanofiber membrane constructs a bionic "spider web structure" electrical signal transmission structure model, such as Figure 1 shown.

[0040] Example 2

[0041] The preparation method of a "spider web structure" nanofiber-based composite material of this embodiment comprises the following steps:

[0042] (1) Preparation of polyacrylamide / sodium alginate / chitosan (PAM / SA / CS) hydrogel solution: Weigh 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA), add 43 mL deionized water, and after complete dissolution, add 0.0215 g ammonium persulfate (APS) and 0.0092 g N,N-methylenebisacrylamide (MBAA) respectively, and add chitosan accounting for 7.5 wt% of the total solid mass, stir at room temperature until completely dissolved, and obtain a PAM / SA / CS hydrogel solution.

[0043] (2) PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 9:1), the mass concentration of PLA spinning solution was 8wt%, and copper sulfate pentahydrate (CuSO4·5H2O) accounting for 5% of the mass of polylactic acid was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of a flow rate of 1mL / h, a voltage of 20kV, a receiving distance of 18cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process must be carried out in the dark to prevent DCM from photocatalytic reaction during the spinning process). During the spinning process, a spray gun (W-101) was used to spray copper conductive ink, spraying once every 50min, and spraying 5 times to obtain Cu doped 2+ Polylactic acid-based copper-plated porous nanofiber membrane. The PAM / SA / CS hydrogel solution was sprayed on the Cu-doped 2+ The polylactic acid-based copper-plated porous nanofiber membrane was dried at 60°C for 45 min, and the dried sample was placed under a UV lamp (power 20 W / cm 2 ) and irradiated for 2 hours.

[0044] Example 3

[0045] The preparation method of a "spider web structure" nanofiber-based composite material of this embodiment comprises the following steps:

[0046] (1) Preparation of polyacrylamide / sodium alginate / chitosan (PAM / SA / CS) hydrogel solution: Weigh 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA), add 43 mL deionized water, and after complete dissolution, add 0.0215 g ammonium persulfate (APS) and 0.0092 g N,N-methylenebisacrylamide (MBAA) respectively, and add chitosan accounting for 7.5 wt% of the total solid mass, stir at room temperature until completely dissolved, and obtain a PAM / SA / CS hydrogel solution.

[0047] (2) PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 9:1), the mass concentration of PLA spinning solution was 8wt%, and copper sulfate pentahydrate (CuSO4·5H2O) accounting for 5% of the mass of polylactic acid was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of a flow rate of 1mL / h, a voltage of 20kV, a receiving distance of 18cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process must be carried out in the dark to prevent DCM from photocatalytic reaction during the spinning process). During the spinning process, a spray gun (W-101) was used to spray copper conductive ink, spraying once every 40min, and spraying 6 times to obtain Cu doped 2+ Polylactic acid-based copper-plated porous nanofiber membrane. The PAM / SA / CS hydrogel solution was sprayed on the Cu-doped 2+ The polylactic acid-based copper-plated porous nanofiber membrane was dried at 60°C for 45 min, and the dried sample was placed under a UV lamp (power 20 W / cm 2 ) and irradiated for 2 hours.

[0048] Example 4

[0049] The preparation method of a "spider web structure" nanofiber-based composite material of this embodiment comprises the following steps:

[0050] (1) Preparation of polyacrylamide / sodium alginate / chitosan (PAM / SA / CS) hydrogel solution: Weigh 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA), add 43 mL deionized water, and after complete dissolution, add 0.0215 g ammonium persulfate (APS) and 0.0092 g N,N-methylenebisacrylamide (MBAA) respectively, and add chitosan accounting for 10 wt% of the total solid mass, stir at room temperature until completely dissolved, and obtain a PAM / SA / CS hydrogel solution.

[0051] (2) PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 8:1), the mass concentration of PLA spinning solution was 9wt%, and copper sulfate pentahydrate (CuSO4·5H2O) accounting for 3% of the mass of polylactic acid was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of a flow rate of 1.5mL / h, a voltage of 18kV, a receiving distance of 17cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process must be carried out in the dark to prevent DCM from photocatalytic reaction during the spinning process). During the spinning process, a spray gun (W-101) was used to spray copper conductive ink, spraying once every 30min, and spraying 6 times to obtain Cu doped 2+Polylactic acid-based copper-plated porous nanofiber membrane. The PAM / SA / CS hydrogel solution was sprayed on the Cu-doped 2+ The polylactic acid-based copper-plated porous nanofiber membrane was dried at 60°C for 40 min, and the dried sample was placed under a UV lamp (power 30 W / cm 2 ) and irradiated for 2 hours.

[0052] Example 5

[0053] The preparation method of a "spider web structure" nanofiber-based composite material of this embodiment comprises the following steps:

[0054] (1) Preparation of polyacrylamide / sodium alginate / chitosan (PAM / SA / CS) hydrogel solution: Weigh 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA), add 43 mL deionized water, and after complete dissolution, add 0.0215 g ammonium persulfate (APS) and 0.0092 g N,N-methylenebisacrylamide (MBAA) respectively, and add chitosan accounting for 8.5 wt% of the total solid mass, stir at room temperature until completely dissolved, and obtain a PAM / SA / CS hydrogel solution.

[0055] (2) PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 7:1), the mass concentration of PLA spinning solution was 8wt%, and copper sulfate pentahydrate (CuSO4·5H2O) accounting for 7% of the mass of polylactic acid was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of a flow rate of 1.3mL / h, a voltage of 19kV, a receiving distance of 15cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process must be carried out in the dark to prevent DCM from photocatalytic reaction during the spinning process). During the spinning process, a spray gun (W-101) was used to spray copper conductive ink, spraying once every 40min, and spraying 6 times to obtain Cu doped 2+ Polylactic acid-based copper-plated porous nanofiber membrane. The PAM / SA / CS hydrogel solution was sprayed on the Cu-doped 2+ The polylactic acid-based copper-plated porous nanofiber membrane was dried at 60°C for 50 min, and the dried sample was placed under a UV lamp (power 20 W / cm 2 ) and irradiated for 2 hours.

[0056] Comparative Example 1

[0057] The preparation method of a nanofiber-based composite material in this comparative example is different from that in Example 1 in that the electrospinning process does not include the process of spraying copper conductive ink. The specific steps are as follows:

[0058] (1) Preparation of polyacrylamide / sodium alginate / chitosan (PAM / SA / CS) hydrogel solution: Weigh 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA), add 43 mL deionized water, and after complete dissolution, add 0.0215 g ammonium persulfate (APS) and 0.0092 g N,N-methylenebisacrylamide (MBAA) respectively, and add chitosan accounting for 10 wt% of the total solid mass, stir at room temperature until completely dissolved, and obtain a PAM / SA / CS hydrogel solution.

[0059] (2) PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 9:1), the mass concentration of PLA spinning solution was 8wt%, and copper sulfate pentahydrate (CuSO4·5H2O) accounting for 5% of the mass of polylactic acid was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The spinning process was carried out under the conditions of a flow rate of 1mL / h, a voltage of 20kV, a receiving distance of 18cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process should be carried out in the dark to prevent DCM from having a photocatalytic reaction during the spinning process), and Cu doped 2+ Polylactic acid porous nanofiber membrane. The PAM / SA / CS hydrogel solution was sprayed on the Cu-doped 2+ The polylactic acid porous nanofiber membrane was dried at 60°C for 45 min, and the dried sample was placed under a UV lamp (power 20 W / cm 2 ) and irradiated for 2 hours.

[0060] Comparative Example 2

[0061] The method for preparing a nanofiber-based composite material in this comparative example is different from that in Example 1 in that a single solvent DMF is used in the electrospinning process, and the specific steps are as follows:

[0062] (1) Preparation of polyacrylamide / sodium alginate / chitosan (PAM / SA / CS) hydrogel solution: Weigh 6.025 g acrylamide (AM) and 0.975 g sodium alginate (SA), add 43 mL deionized water, and after complete dissolution, add 0.0215 g ammonium persulfate (APS) and 0.0092 g N,N-methylenebisacrylamide (MBAA) respectively, and add chitosan accounting for 10 wt% of the total solid mass, stir at room temperature until completely dissolved, and obtain a PAM / SA / CS hydrogel solution.

[0063] (2) PLA particles were dissolved in DMF solvent, the mass concentration of PLA spinning solution was 8wt%, and copper sulfate pentahydrate (CuSO4·5H2O) accounting for 5% of the mass of polylactic acid was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of flow rate of 1mL / h, voltage of 20kV, receiving distance of 18cm, ambient temperature of (25±1)℃, and relative humidity of 55%±1%. During the spinning process, copper conductive ink was sprayed with a spray gun (W-101) at an interval of 60min to obtain Cu doped 2+ Polylactic acid-based copper-plated porous nanofiber membrane. The PAM / SA / CS hydrogel solution was sprayed on the Cu-doped 2+ The polylactic acid-based copper-plated porous nanofiber membrane was dried at 60°C for 45 min, and the dried sample was placed under a UV lamp (power 20 W / cm 2 ) and irradiated for 2 hours.

[0064] Comparative Example 3

[0065] A doped Cu 2+ The method for preparing the polylactic acid-based copper-plated porous nanofiber membrane is different from that of Example 1 in that it does not include spraying the PAM / SA / CS hydrogel solution and the subsequent cross-linking process, and the specific steps are as follows:

[0066] PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 9:1), the mass concentration of PLA spinning solution was 8wt%, and 5% copper sulfate pentahydrate (CuSO4·5H2O) was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of a flow rate of 1mL / h, a voltage of 20kV, a receiving distance of 18cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process needs to be carried out in the dark to prevent DCM from photocatalytic reaction during the spinning process). During the spinning process, a spray gun (W-101) was used to spray copper conductive ink, and the spraying was performed once every 60min to obtain Cu doped 2+ Polylactic acid-based copper-coated porous nanofibrous membrane.

[0067] Comparative Example 4

[0068] The preparation method of a nanofiber-based composite material in this comparative example is different from that in Example 1 in that the spraying of the PAM / SA / CS hydrogel solution and the subsequent cross-linking process are changed to PDMS curing and encapsulation. The specific steps are as follows:

[0069] PLA particles were dissolved in a mixed solvent of DCM and DMF (DCM / DMF, 9:1), the mass concentration of PLA spinning solution was 8wt%, and 5% copper sulfate pentahydrate (CuSO4·5H2O) was added to the spinning solution, and stirred for 6 hours at room temperature in the dark. The process was carried out under the conditions of a flow rate of 1mL / h, a voltage of 20kV, a receiving distance of 18cm, an ambient temperature of (25±1)℃, and a relative humidity of 55%±1% (the spinning process needs to be carried out in the dark to prevent DCM from photocatalytic reaction during the spinning process). During the spinning process, a spray gun (W-101) was used to spray copper conductive ink, and the spraying was performed once every 60min to obtain Cu doped 2+ Polylactic acid-based copper-plated porous nanofiber membrane: 10g PDMS and 1g curing agent were mixed, stirred evenly, and ultrasonically vibrated for 20 minutes to defoam, and then the composite fiber membrane was placed in the PDMS solution, dried and cured at 80°C for 2 hours.

[0070] Test Case

[0071] The surface morphology, contact angle, mechanical properties, resistance and sensitivity of the "spider web structure" nanofiber-based composite material prepared by the present invention were tested and analyzed as follows:

[0072] Figure 2 The SEM morphology of the "spider web structure" nanofiber-based composite material prepared by the present invention shows that there are many and obvious pores on the surface of the nanofibers. This is because according to the principle of like dissolves like, DCM is selected as the solvent, DMF is selected as the non-solvent and PLA is used to form a non-solvent solution (NSS) system. The rapid volatilization of DMF and the volatilization of the DCM-enriched phase form PLA porous nanofibers. However, the fiber surface is rough and no particles are observed. This is because during the electrospinning process, Cu 2+ are wrapped and dispersed in the PLA matrix. In addition, the pores on the fiber surface are uneven and regular because Cu 2+ The addition of leads to an increase in the conductivity of the spinning solution, and the amount of charge carried by the jet increases during electrospinning, thereby enhancing the instability of the jet, making it difficult for the solvent to completely evaporate, affecting the pore structure and fiber formation. The copper solution is deposited on the surface of the nanofibers by spraying. SEM images show that Cu is deposited on the surface of the skeleton nanofibers in a discontinuous sheet structure, which helps to form more Cu metal heterojunctions and is beneficial to regulating the conductivity of the PLA-based nanofiber membrane.

[0073] The porosity and contact angle tests were performed on the "spider web structure" nanofiber-based composite material prepared by the present invention. The porosity and contact angle tests are used to evaluate the wettability, adsorption capacity, liquid permeability, etc. of the material surface to liquids, which in turn affects the realization of specific functions of flexible intelligent wearable devices. The greater the porosity of the material surface, the smaller the contact angle, the better its hydrophilicity, and vice versa, the worse its hydrophilicity. Figure 3 The porosity and contact angle of the composite materials prepared in Example 1 and Comparative Example 2 are compared. It can be seen that the porosity of Example 1 is larger than that of Comparative Example 2, and the contact angle is smaller. With the increase of porosity, the specific surface energy of the material will also increase, the hydrophilicity will be enhanced, the contact angle will decrease, and the doped Cu 2+ It has a certain degree of hydrophilicity, which is conducive to improving hydrophilicity. Fiber materials with high porosity can usually absorb more liquid and show good wettability. This structure is conducive to the copper conductive ink forming a "linear continuous conductive area" on the fiber surface, and enriching it at the fiber junction to form a "sheet conductive area". Thus, an electrical signal transmission network model similar to the bionic "spider web structure" is constructed.

[0074] Figure 4 It is the anti-bending length of the nanofiber-based composite material prepared in Example 1 and Comparative Example 4. The anti-bending length C is also called stiffness, which is an index of the rigidity and flexibility of the fabric. The larger the C value, the stiffer and less flexible the fabric is, and the softer it is. The specific testing process is as follows: Cut the sample into a strip with a length × width of 150mm × 20mm, place it on a trapezoidal wooden block with a bevel angle θ=60°, and place a scale on the sample to ensure that it is flush with the head end of the strip. During measurement, push the scale bar out at a uniform speed, and the scale bar drives the spline to be pushed out synchronously until the spline sags due to its own weight and touches the bevel. At this moment, the anti-bending length C (cm) can be calculated from the length l0 pushed out from the scale and the bevel angle θ: After 20 tests and averaging, it can be seen that the bending length of Example 1 is only 0.99 cm, indicating that the composite material has high softness and good skin adhesion, and is suitable for health monitoring. However, the bending length of Comparative Example 4 reaches 5.94 cm, which has poor softness and low biocompatibility, and is not suitable for monitoring under slight deformation.

[0075] The mechanical properties of the "spider web structure" nanofiber-based composite materials prepared in Examples 1-3 and the samples of Comparative Examples 1, 3, and 4 were tested. The specific testing process is as follows: the samples were made into strips with a length × width of 50 mm × 10 mm, and the mechanical properties of the samples were tested using an AI-7000S1 high-speed rail detector with a clamp distance of 30 mm and a test speed of 50 mm / min. A tensile test was performed, and multiple measurements were taken to take the average value. Figure 5The stress-strain curve of the prepared "spider web structure" nanofiber-based composite material. It can be seen from the figure that after spraying the PAM / SA / CS hydrogel solution, the elongation at break of the composite material increased from 10% (Comparative Example 3) to 51% (Example 1). After spraying the copper conductive ink, the fracture strength of the composite material is improved; as the time interval of spraying the copper conductive ink gradually decreases, more Cu is deposited on the surface of the skeleton nanofibers, and the elongation at break of the composite material gradually decreases. This is because copper is a rigid material, and its addition will reduce the flexibility of the material. After PDMS encapsulation (Comparative Example 4), the elongation at break of the composite material is 24%, which improves the ductility of the overall material, making it easier to deform when stretched. Under larger strains, the material may show a strain hardening effect. The encapsulated material can deform with a larger strain after being stressed, which increases the elongation at break.

[0076] Figure 6 The resistance of the nanofiber-based composite material of the "spider web structure" prepared in Examples 1-3 and the samples of Comparative Examples 1, 3 and 4 can be seen. The resistance of Comparative Example 3 is the smallest, only 40.2 ohms. Copper is an excellent conductive material with a high free electron density, which can quickly conduct electrical signals and show a low ohmic resistance. The resistance of Example 1 is 77.3 ohms, which is an increase compared with Comparative Example 3. This is because there is a solid-liquid interface or a semi-solid-solid interface between the hydrogel and the copper conductive ink. The interface effect usually introduces additional resistance, especially when the conduction mechanism between different materials is different (copper is electronically conductive and hydrogel is ionically conductive). The presence of this interface resistance will further increase the total resistance and affect the conduction efficiency. However, as the time interval of spraying the copper conductive ink gradually decreases, the resistance of the composite material gradually decreases (77.3-62.4 ohms). This is because more Cu is deposited on the surface of the skeleton nanofibers in a sheet structure, forming a more stable conductive layer structure. The resistance of Comparative Example 1 is 4972 kilo-ohms because it relies entirely on hydrogel for conductivity. The conductivity of hydrogel is far inferior to that of metallic copper. It mainly conducts current through ions. There is a large amount of water and polymer molecular chains inside, which hinder the free migration of ions, resulting in a longer conductive path, greater resistance, and a significant increase in resistance. After PDMS encapsulation, the resistance reaches 6065 kilo-ohms. Since PDMS itself is an electrical insulating material, its high resistance property is due to the lack of freely moving charge carriers in its polymer structure. This makes the conductivity of PDMS very low when it is not doped with conductive fillers, thereby greatly reducing the conductivity of the composite material.

[0077] Figure 7The sensitivity of the nanofiber-based composite materials of the "spider web structure" prepared in Examples 1-3 and the samples of Comparative Examples 1, 3 and 4 is as follows: the samples are made into strips with a length × width of 50 mm × 10 mm, and the resistance is measured by a 2400 digital source meter of Geely Technology Co., Ltd. in the United States, and the resistance change rate under the stretched state is tested, wherein the slope of the strain-resistance change rate curve is the sensitivity (GF) corresponding to the sample. It can be seen from the figure that within the strain range of 0-10%, the sensitivity of Comparative Example 3 is as high as 61.3, and within the entire strain range, the resistance change rate increases with the increase of strain, which indicates that the PLA-based nanofiber membrane has excellent sensitivity and can effectively detect the change of strain and respond in time; the sensitivity of Example 1 is 30.2, which is lower than that of Comparative Example 3, mainly due to the presence of the hydrogel layer. Although the hydrogel has certain flexibility and ionic conductivity, its conductive performance is far inferior to that of copper conductive ink. The presence of hydrogel introduces additional resistance in the process of electrical signal transmission, which reduces the efficiency of electrical signal transmission. In addition, the flexibility of hydrogel may absorb part of the deformation under stress, resulting in the conductive ink layer failing to fully respond to external stress, thereby reducing the overall sensitivity. However, its multilayer structure provides a certain balance between flexibility and functionality, and as the time interval of spraying copper conductive ink gradually decreases, the sensitivity of the composite material gradually increases. This is because more Cu is deposited on the surface of the skeleton nanofiber in a sheet structure, forming more Cu metal heterojunctions and a more stable conductive layer structure. During the stretching process, as the strain increases, the Cu metal heterojunction will slide with the fiber, and the conductive network will be slowly disconnected, reducing the contact area between the Cu metal heterojunctions. In the process of increasing strain, the contact of the Cu metal heterojunction is completely disconnected. At this time, the sensing mechanism also changes from the disconnection mechanism to the tunneling effect, so there will be a difference in the electrical signal, thereby affecting the sensitivity of strain sensing. The sensitivity of Comparative Example 1 is 0.0014. This result shows that the hydrogel layer lacking copper conductive ink can hardly conduct electricity effectively. The conductive mechanism of hydrogel relies on ionic conduction, which is far less efficient than electronic conduction. Due to the weak conductivity of hydrogel and the lack of efficient conductive paths, the resistance change is almost imperceptible, resulting in extremely low sensitivity. This shows that it is difficult to achieve high-performance flexible sensor design relying solely on hydrogel materials. The sensitivity of the sample encapsulated with PDMS is almost zero because the high resistance of PDMS (6065 kilo-ohms) makes it difficult for current to flow in the material, and the lack of sufficient current response changes leads to insufficient response of the sensor to changes in external signals (such as strain or pressure), which directly affects the sensitivity.

[0078] Figure 8This is the anti-fatigue performance test curve of the "spider web structure" nanofiber-based composite material prepared in Example 1. The specific test process is as follows: the sample is made into a strip with a length × width of 50mm × 10mm, and the two ends are connected with thin copper wires, and the terminal is fixed with double-sided conductive copper tape, and then the other end of the thin copper wire is connected to the wire of the resistance tester. The whole connection constitutes a closed loop, and the sample is fixed on the AI-7000S1 high-speed rail detector. A cyclic tensile test with a fixed elongation of 20% is performed for 1000 times to obtain its resistance change. It can be seen from the figure that during multiple large strain tensile tests, the electrical signal output by the composite material is relatively stable, and it has the characteristics of anti-fatigue and long-term service.

[0079] Application Examples

[0080] The "spider web structure" nanofiber-based composite material prepared by the present invention can be applied to human motion and physiological health monitoring signals. The specific testing process is as follows: Attach the sample to different positions of the human body, and use a 2400 digital source meter to perform physiological monitoring (such as pulse, heart rate, breathing, etc.) and motion detection (such as finger movement, wrist bending, elbow movement, etc.) of the human body. The electrode wiring method is: stick the composite material sample to different parts of the human body that need to be tested, connect the two ends with thin copper wires, fix the wiring terminals with double-sided conductive copper tape, and then connect the other end of the thin copper wire to the wire of the resistance tester. The entire connection constitutes a closed loop, thereby testing the sensing performance. The results are as follows: Figure 9-10 As shown in the figure, when the composite material sample is attached to the finger joints, wrists, elbows, and knees, the resistance change rate of the composite material sensor increases with the increase of the bending angle of the wrist, elbow, and knee; the resistance change rate decreases with the decrease of the bending angle; and after repeated bending, the resistance change rate can make corresponding changes in time, and the trend of the resistance change rate corresponding to each bending remains unchanged and almost stable. At the same time, the composite material sensor is used to monitor the human pulse and heartbeat, and it is found that tiny strains can also be detected and responded.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a "spider web structure" nanofiber-based composite material, characterized in that: Here are the steps: (1) Preparation of doped Cu by electrospinning 2+ Polylactic acid porous nanofiber membrane was sprayed with copper conductive ink during electrospinning to prepare Cu-doped 2+ Polylactic acid-based copper-coated porous nanofiber membrane; (2) Spray the polyacrylamide / sodium alginate / chitosan hydrogel solution onto the Cu-doped 2+ The polylactic acid-based copper-plated porous nanofiber membrane is then dried and UV-crosslinked to obtain a "spider web structure" nanofiber-based composite material.

2. The preparation method according to claim 1, characterized in that: The spinning solution for electrospinning in step (1) is prepared by dissolving polylactic acid and copper sulfate pentahydrate in a mixed solvent of dichloromethane and N,N-dimethylformamide.

3. The preparation method according to claim 2, characterized in that: The mass ratio of dichloromethane to N,N-dimethylformamide is (7-9):1; the concentration of polylactic acid in the spinning solution is 8-9wt%, and copper sulfate pentahydrate accounts for 3-7wt% of the mass of the polylactic acid.

4. The preparation method according to claim 1, characterized in that: The electrospinning process parameters in step (1) are: flow rate of 1-1.5 mL / h, voltage of 18-20 kV, receiving distance of 15-18 cm, ambient temperature of (25±1)° C., relative humidity of 55%±1%, and spinning in the dark.

5. The preparation method according to claim 4, characterized in that: The interval for spraying the copper conductive ink in the step (1) is one spraying every 30-60 minutes, and the spraying is 4-6 times.

6. The preparation method according to claim 5, characterized in that: The preparation method of the polyacrylamide / sodium alginate / chitosan hydrogel solution in step (2) is as follows: acrylamide and sodium alginate are dissolved in deionized water, and ammonium persulfate, N,N-methylenebisacrylamide and chitosan are added thereto to obtain the polyacrylamide / sodium alginate / chitosan hydrogel solution.

7. The preparation method according to claim 6, characterized in that: The content of chitosan accounts for 7.5-10wt% of the total solid mass.

8. The preparation method according to claim 5, characterized in that: The drying temperature in step (2) is 60°C and the drying time is 40-50 minutes; the power of the UV lamp in the UV crosslinking is 20-30W / cm 2 , the cross-linking time is 2h.

9. A nanofiber-based composite material with a "spider web structure" prepared by the preparation method described in any one of claims 1 to 8.

10. Application of the "spider web structure" nanofiber-based composite material according to claim 9 in strain sensors.

Citation Information

Patent Citations

  • Preparation method of flexible capacitive pressure sensor

    CN115096480A

Cited By

  • Self-adaptively fixed blood coagulation monitoring flexible pressure sensor and preparation method and application thereof

    CN120570577A

  • Strain sensor and application thereof in gesture recognition and silent language recognition

    CN122429699A